Physique and body composition in soccer players across adolescence - Nikolaidis, P. T.; Karydis, N. V. (Asian Journal of Sports Medicine, 2011)
Purpose: Although the contribution of physique and body composition in soccer performance was recognized, these parameters of physical fitness were not well-studied in adolescent players. Aim of this study was to investigate physique and body composition across adolescence. Methods: Male adolescents (N=297 aged 12.01-20.98 y), classified into nine one-year age-groups, child (control group, N=16 aged 7.34-11.97 y) and adult players (control group, N=29 aged 21.01-31.59 y), all members of competitive soccer clubs, performed a series of anthropometric measures (body mass, height, skinfolds, circumferences and girths), from which body mass index (BMI), percentage of body fat (BF%), fat mass (FM), fat free mass (FFM) and somatotype (Heath-Carter method) were calculated. Results: Age had a positive association with FM (r=0.2, P<0.001) and FFM (r=0.68, P<0.001), and a negative association with BF (r=-0.12, P=0.047). Somatotype components changed across adolescence as well; age was linked to endomorphy (r=-0.17, P=0.005), mesomorphy (r=0.14, P=0.019) and ectomorphy (r=-0.17, P=0.004). Compared with age-matched general population, participants exhibited equal body mass, higher stature, lower body mass index and lower BF. Conclusions: During adolescence, soccer players presented significant differences in terms of body composition and physique. Thus, these findings could be employed by coaches and fitness trainers engaged in soccer training in the context of physical fitness assessment and talent identification.